The Influence of Brand Ambassador, Price, and Advertising Content on Repurchase Intention through Customer Trust as an Intervening Variable - ningrum, vika fhidya; Prabowo, Heri; Kurniawan, Bayu (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to determine the Influence of Brand Ambassador, Price, and Advertising Content on Repurchase Intention through Customer Trust as an Intervening Variable among Blibli E-Commerce Consumers in Semarang City. The sample in this study consisted of 180 respondents, selected using a purposive sampling method. The research data were processed using SEM AMOS 24. The results of the study are as follows: (1) The influence of brand ambassador on customer trust is rejected, (2) The influence of price on customer trust is rejected, (3) The influence of advertising content on customer trust is accepted, (4) The influence of advertising content on repurchase intention is rejected, (5) The influence of brand ambassador on repurchase intention is rejected, (6) The influence of customer trust on repurchase intention is accepted, (7) The influence of price on repurchase intention is rejected, (8) The influence of brand ambassador on repurchase intention with the mediation of customer trust is proven, (9) The influence of price on repurchase intention with the mediation of customer trust is proven, (10) The influence of advertising content on repurchase intention with the mediation of customer trust is proven.